Radial extracorporeal shockwave therapy on calcaneal spurs: a randomized controlled trial (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND The effectiveness of extracorporeal shockwave therapy (ESWT) in handling pain and calcaneal spurs is still controversial, whereas research on the effectiveness of ESWT in the reactive ossification process of calcaneal spurs, involving osteoprotegerin (OPG) and the receptor activator of nuclear factor-kappa B (RANK), does not exist. This study was aimed to assess the effect of ESWT on pain, the length of the spur, plasma OPG and RANK level on the calcaneal spur. METHODS This study was a randomized controlled trial in patients with calcaneal spurs. ESWT was administered at the pain point by applying 2,000 shocks, at an intensity of 2 bars, given six times with a 7â–10-day interval. The visual analog scale (VAS) data, plasma OPG and RANK level were analyzed using Mann–Whitney U test, whereas spur size was analyzed using chi-square test. RESULTS One month after therapy at rest (p < 0.001) and when walking after getting up (p = 0.020), the VAS was lower than that in the control group. The plasma OPG level was lower than control group shortly after therapy (p < 0.001). The plasma RANK level was higher than control group shortly after therapy (p < 0.001). ESWT did not affect the reduction of spur measurement (p = 0.382). CONCLUSIONS ESWT reduced pain, decreased plasma OPG level, and increased plasma RANK level. Although ESWT did not have any effect on spur reduction, it affected plasma OPG and RANK level that play a role in the activity of osteoblasts and osteoclasts.